Glass structure and ion dynamics of lead-cadmium fluorgermanate glasses - Tambelli, C. C.; Donoso, J. P.; Magon, C. J.; Bueno, L. A.; Messaddeq, Younes [UNESP]; Ribeiro, SJL; de Oliveira, LFC; Kosacki, I (American Institute of Physics (AIP), 2004)
Glass structure and fluorine motion dynamics are investigated in lead-cadmium fluorgermanate glasses by means of differential scanning calorimetry, Raman scattering, x-ray absorption (EXAFS), electrical conductivity (EC), and F-19 nuclear magnetic resonance (NMR) techniques. Glasses with composition 60PbGeO(3)-xPbF(2)-yCdF(2) (in mol %), with x+y=40 and x=10, 20, 30, 40, are studied. Addition of metal fluorides to the base PbGeO3 glass leads to a decrease of the glass transition temperature (T-g) and to an enhancement of the ionic conductivity properties. Raman and EXAFS data analysis suggest that metagermanate chains form the basic structural feature of these glasses. The NMR study leads to the conclusion that the F-F distances are similar to those found in pure crystalline phases. Experimental results suggest the existence of a heterogeneous glass structure at the molecular scale, which can be described by fluorine rich regions permeating the metagermanate chains. The temperature dependence of the NMR line shapes and relaxation times exhibits the qualitative and quantitative features associated with the high fluorine mobility in these systems. (C) 2004 American Institute of Physics.